Meniscus Ripstop Stitches: A Useful Technique for Arthroscopic Repair of Challenging Radial Tears of the Meniscus - Fabien Meta, M.D.; Alexander C. Hayden, M.D.; Xuankang Pan, B.S.; Mario Hevesi, M.D., Ph.D.; Adam J. Tagliero, M.D.; Aaron J. Krych, M.D. (Arthroscopy Techniques)
Radial meniscal tears can be challenging to address and require advanced arthroscopic techniques for satisfactory repair. When radial tears occur in older patients, the surgeon often encounters suboptimal tissue integrity that presents its own challenges. Incorporating ripstop sutures in tie-grip repair constructs for radial tears has been documented in the literature with favorable biomechanical properties. This Technical Note and accompanying video present a reproducible method for incorporating tie-grip and mobile ripstop stitches to fortify traditional meniscal repair configurations for radial tears. This technique augments the biomechanical strength of repair and may prove useful in poor tissue quality and areas of small focal deficiency, especially in scenarios with repairable but degenerative meniscal tissue. This is particularly relevant considering many repairs fail due to pull-through of sutures within the meniscal tissue.